Hepatocyte apoptosis in dairy cattle during the transition period - Tharwat, Mohamed (Canadian Veterinary Medical Association, 2012)
The objective of this study was to investigate hepatocyte apoptosis in dairy cows during the transition period. Four clinically healthy, pregnant dairy cattle were used. The cows had no clinical diseases throughout this study. Blood samples were collected and livers were biopsied from the cows at 3 different times: 3 weeks before expected partition (wk −3); during parturition (wk 0), and 3 weeks (wk +3) after parturition. The damage to deoxyribonucleic acid (DNA) caused by hepatocytes was evaluated by comet assay. The apoptotic features of hepatocytes were examined by immunohistochemistry and electron microscopic analyses. The hepatic triglyceride content markedly increased at wk 0 and wk +3 compared with the values at wk −3. The results of the comet assay showed increases in the mean tail moment values of hepatic cells after parturition in all cows, which suggested increased DNA damage. Histopathologically, the hepatocytes began to contain lipid droplets at wk 0 and were severely opacified at wk +3. Caspase-3-positive and single-stranded DNA-(ssDNA)-positive cells were first detected in the liver after parturition. Condensation of nuclear chromatin, a typical sign of apoptosis, was confirmed by transmission electron microscopy after parturition. These results suggest that apoptosis is induced in hepatocytes of dairy cows around parturition and may result from lipotoxicity in hepatocytes.